2017
DOI: 10.1080/14728222.2017.1279146
|View full text |Cite
|
Sign up to set email alerts
|

The NR4A subfamily of nuclear receptors: potential new therapeutic targets for the treatment of inflammatory diseases

Abstract: Prolonged inflammatory response contributes to the pathogenesis of chronic disease-related disturbances. Among nuclear receptors (NRs), the orphan NR4A subfamily, which includes Nur77 (NR4A1), Nurr1 (NR4A2) and NOR1 (NR4A3), has recently emerged as a therapeutic target for the treatment of inflammation. Areas covered: This review focuses on the capacity of NR4A receptors to counter-regulate the development of the inflammatory response, with a special focus on the molecular transrepression mechanisms. Expert op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 153 publications
2
76
0
Order By: Relevance
“…which have potential to directly degrade the TLR-signaling molecules involved in MyD88-dependent or TRIF-dependent and MyD88independent TLR signaling. However, it is impossible to describe all the endogenous negative regulators of TLR signaling here in this manuscript whose detail can be found somewhere else [466][467][468][469][470].…”
Section: Current and Future Tlr Based Therapeuticsmentioning
confidence: 99%
“…which have potential to directly degrade the TLR-signaling molecules involved in MyD88-dependent or TRIF-dependent and MyD88independent TLR signaling. However, it is impossible to describe all the endogenous negative regulators of TLR signaling here in this manuscript whose detail can be found somewhere else [466][467][468][469][470].…”
Section: Current and Future Tlr Based Therapeuticsmentioning
confidence: 99%
“…It is possible that the insulin‐resistant skeletal muscle in OB and T2DM subjects present with translational repression of Nur77 and NOR1 (Rodriguez‐Calvo et al. ). To compensate for this inability to translate the gene responses into functional protein, OB and T2DM skeletal muscle may bolster Nur77 and NOR1 gene expressions in response to insulin stimulation, without concomitant increases in protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…In NOR1 knockout SMCs, PDGF‐induced proliferation and migration is almost completely inhibited, which coincides with a strong reduction in cyclin D1 expression (Nomiyama et al, ). Since the expression and roles of NR4A family are context‐ and tissue‐specific (Rodríguez‐Calvo, Tajes, & Vázquez‐Carrera, ), and the role of NOR1 in ASM biology has not been explored thus far, we attempted to investigate the expression and role of NOR1 in ASMC function. In the current study, we found that NOR1 is highly expressed in human ASMCs and its expression is markedly induced by PDGF‐BB stimulation and inhibited by miR‐638, which is consistent with our previous notion showing that miR‐638 directly binds to the 3′‐UTR of human NOR1 mRNA and downregulates its expression in vascular SMCs (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%